Hubungan Tingkat Pengetahuan Ibu Tentang Karies Gigi Pada Anak Usia Prasekolah di TK Al-Muttaqien Bandung - Dhea Rania Putri; Isa Insanuddin; Deden Ridwan Chaeruddin; Devy Octaviana (Jurnal Terapi Gigi dan Mulut, 2022)
In general, children's oral hygiene is worse and children eat more food and drinks that cause caries. Children generally like sweet foods such as biscuits, chocolate, if the child eats too much sweet food and rarely cleans it, then his teeth have a lot of caries. This study aims to determine the relationship between mother's level of knowledge about dental caries in preschool children in kindergarten. Al-Muttaqien Bandung. This research is a quantitative analytical research. This research was conducted in February-May 2022, by conducting direct examinations on children and filling out questionnaires. The sampling technique was carried out using the purposive sampling technique with a sample of 30 respondents. Data processing was carried out quantitatively by collecting data on caries def-t in preschool-aged children and filling out knowledge questionnaires for mothers. The results of the study regarding the relationship between the mother's level of knowledge about dental caries in preschool age children in kindergarten Al-Muttaqien Bandung, a high level of maternal knowledge as many as 26 people with a percentage of 86,7% and a caries index with a very low category of 10 people with a percentage of 33,3%, which states that there is a relationship between the level of knowledge of mothers about dental caries in preschool age children in kindergarten Al-Muttaqien Bandung.